1971
DOI: 10.1161/01.cir.44.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parasympathetic Inhibition in the Hyperkinetic Type of Borderline Hypertension

Abstract: Eleven patients with borderline hypertension and high cardiac output were compared to 16 paid healthy volunteers. Cardiac output, heart rate, and intraarterial blood pressure were determined at rest, after administration of 0.2 mg/kg of propranolol i.v., and after administration of an additional 0.04 mg/kg of atropine. In four additional patients, response to infusion of isoproterenol before and after administration of 0.2 mg/kg of propranolol i.v. was evaluated. Resting heart rate and cardiac output in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
0
3

Year Published

1974
1974
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(124 citation statements)
references
References 15 publications
7
111
0
3
Order By: Relevance
“…Adding handgrip exercise to beta blockade further increased resistance but did not increase wave reflections. One explanation for this finding is that handgrip exercise produces a localized increase in resistance (26) (27) found that elevated resting cardiac outputs and heart rates in a group of patients with borderline hypertension were partially normalized after propranolol infusion but were only completely normalized when atropine was added to the beta blockade. More recently, Levenson et al.…”
Section: Methodsmentioning
confidence: 99%
“…Adding handgrip exercise to beta blockade further increased resistance but did not increase wave reflections. One explanation for this finding is that handgrip exercise produces a localized increase in resistance (26) (27) found that elevated resting cardiac outputs and heart rates in a group of patients with borderline hypertension were partially normalized after propranolol infusion but were only completely normalized when atropine was added to the beta blockade. More recently, Levenson et al.…”
Section: Methodsmentioning
confidence: 99%
“…instead, numerous studies in young adults with borderline hypertension have demonstrated that cardiac output and heart rate are elevated and that isH is the predominant Bp phenotype. [34][35][36][37][38] the elevated cardiac output is believed to be neurogenic, involving both the sympathetic 36,39 and parasympathetic nervous systems. 35 indeed, the weight of evidence suggests marked sympathetic nervous system activation in the early stages of essential hypertension, especially in younger subjects.…”
Section: Mechanisms Of Ish In Young Peoplementioning
confidence: 99%
“…More than 25 years ago, for example, Julius and coworkers 5 showed that the elevated resting heart rate values of borderline-hypertensive subjects were reduced by the intravenous administration of a ␤-blocking drug (propranolol) to a more marked degree than the lower heart rate of normotensive controls, suggesting that in the early hypertensive stage, cardiac sympathetic drive is enhanced. They further showed that after the subsequent intravenous injection of a muscarinic receptor antagonist (atropine), the increase in heart rate was less in borderlinehypertensive than in normotensive individuals, supporting the concept that at the cardiac level, an enhanced sympathetic drive combines with a reduced parasympathetic one to make the abnormality of neural cardiac control of borderline hypertensives a composite one.…”
Section: Evidence For Sympathetic Activationmentioning
confidence: 99%